Peranan Pupuk Organik Dari Pelepah Sawit Pada Budidaya Tanaman Kedelai Pada Lahan Sawah - Sunarti Sunarti; Ikhsan Hasibuan; Eka Suzanna (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2017)
Oil palm fronds have huge potential to be developed as a source of organic fertiliser by chopping hard frond to become soft smooth pieces and ready to be proceed in bokashi fertilising system. This research aimed to evaluate the application of oil palm frond organic fertiliser on soybean growth and yield compared to cow manure and chemical fertilisers. Three levels of Nitrogen were applied 60, 90 and 120 kg of N/ha. This study had been done in Padang Rambun village, Seluma District, Bengkulu Province under wet land rice field condition and using rice-soybean rotation. Split plot design and least significant design (LSD) 5% were applied to analyse the data. The results showed that kinds and dosage levels gave very significant effect to all parameters but there was no significant effect between them. LSD analysis proved that oil palm frond organic fertiliser was better than manure bokashi in term of plant height and number of pods but had no significant effect on weight of seeds per plot. Furthermore, increasing of nitrogen level improved growth and yield of soybean meaning that the dosage given did not meet the optimum level for soybean growth and yield.